Study on Student’s Perception about Internship Program and its impact on Their Personality, with reference to Hotel Business Program students Podomoro University - Windawaty, Herry (KONTAN: Jurnal Ekonomi, Manajemen dan Bisnis, 2023)
This study examines the benefits and impact of internships for students in the Hotel Business Program at Podomoro University. The research looks at how internships provide real-world experience, build professional connections, and aid in exploring career options. It also highlights the importance of industry experience for academic education in the hospitality field. The study specifically focuses on factors that influence internship preference among hospitality students, comparing preference for international versus domestic internships, and examining the impact of internships on the personality development of students. The research used is descriptive and the population studied were 75 students who had completed internships in various hotels in Indonesia or abroad. The results show that internships provide valuable opportunities for students to acquire new skills and knowledge, with the internship department playing a crucial role in overseeing and supporting students. Additionally, obtaining an internship at an international chain hotel is highly valued by students and pre-internship seminars are crucial in preparing students for the internship experience.ABSTRAKPenelitian ini mengkaji manfaat dan dampak magang bagi mahasiswa Program Studi Bisnis Perhotelan Podomoro University. Penelitian ini melihat bagaimana magang memberikan pengalaman dunia nyata, membangun koneksi profesional, dan membantu dalam mengeksplorasi pilihan karir. Penelitian ini juga menyoroti pentingnya pengalaman industri untuk pendidikan akademis di bidang perhotelan. Penelitian ini secara khusus berfokus pada faktor-faktor yang mempengaruhi preferensi magang di kalangan mahasiswa perhotelan, membandingkan preferensi magang internasional dan magang domestik, serta meneliti dampak magang terhadap pengembangan kepribadian mahasiswa. Penelitian yang digunakan adalah deskriptif dan populasi yang diteliti adalah 75 mahasiswa yang telah menyelesaikan magang di berbagai hotel di Indonesia maupun di luar negeri. Hasil penelitian menunjukkan bahwa magang memberikan kesempatan yang berharga bagi mahasiswa untuk memperoleh keterampilan dan pengetahuan baru, dengan departemen magang memainkan peran penting dalam mengawasi dan mendukung mahasiswa. Selain itu, mendapatkan kesempatan magang di hotel jaringan internasional sangat dihargai oleh para mahasiswa dan seminar pra-magang sangat penting dalam mempersiapkan mahasiswa untuk pengalaman magang.